2016 Acute Flaccid Myelitis Outbreak in Texas: Promising Outcomes. (4th October 2017) - Quick, Rachel; Mcelvain, Dawn; Patel, Bhairav; Bailey, Ann; Murphey, Donald; Fernandez, Marisol; Kane, Jeffrey; Hauger, Sarmistha
Abstract: Background: In 2014, the United States saw an unprecedented rise in cases of acute flaccid myelitis (AFM). Causes and treatment of AFM are unknown, though it has been linked to enterovirus D68 (EV-D68). Poor outcomes were observed in 2014, with only 5% showing complete recovery of symptoms. During the year 2016, a new outbreak of AFM occurred that surpassed that of 2014. In this outbreak we saw a larger portion of cases in Texas and the disease did not coincide temporally with an EV-D68 outbreak as it did in 2014. We reviewed cases of AFM in Central Texas during 2016 to describe presentation, possible causes, treatments, and outcomes. Methods: Cases of AFM, defined as sudden onset limb weakness and abnormal spinal magnetic resonance imaging involving gray matter, were manually reviewed May 2016-April 2017. Information included extensive review of presentation, imaging, laboratory values, treatment and response, and neurology follow up and outcomes. Results: AFM was identified in 7 cases. Median age was 4.4 years. Cervical spinal involvement and cerebrospinal fluid pleocytosis (>5 white blood cells/mm 3 ) were present in all cases. Fever and respiratory illness were the most common prodromal symptoms (71% each). Medical treatments varied; use and response are represented in Figure 1. All children received physical/occupational therapy. A possible etiology was found in 4 cases; one with EV-D68. The remaining 3 cases tested positive for enterovirus A71 and human parechovirus (HPeV), HPeV alone, and human herpesvirus-6 (HHV-6). Three of the 7 cases regained full function at 9–30 weeks after onset of illness, including the cases diagnosed with HHV-6 and HPeV only; the remaining 4 all showed improvement with residual functional impairment at 4.5–9 months. Neither case with concomitant enterovirus has recovered fully; the case with EV-D68 suffered the most severe disease. Conclusion: AFM continues to be a complex, poorly understood disease. Although there are no treatment standards, our data show promising symptom improvement. One case (14%) was diagnosed with EV-D68 compared with 22% of cases tested in the U.S. in 2014. Disclosures: All authors: No reported disclosures.